Use of the 2-Pyridinealdoxime/N,N′-Donor Ligand Combination in Cobalt(III) Chemistry: Synthesis and Characterization of Two Cationic Mononuclear Cobalt(III) Complexes - Konstantis F. Konidaris; Catherine P. Raptopoulou; Vassilis Psycharis; Spyros P. Perlepes; Evy Manessi-Zoupa; Theocharis C. Stamatatos (Bioinorganic Chemistry and Applications)
The use of 2-pyridinealdoxime (paoH)/N,N′-donor ligand (L-L) “blend” in cobalt chemistry has afforded two cationic mononuclear cobalt(III) complexes of the general type [Co(pao)2(L-L)]+, where L-L = 1,10-phenanthroline (phen) and 2,2′-bipyridine (bpy). The CoCl2/paoH/L-L (1 : 2 : 1) reaction system in MeOH gives complexes [CoIII(pao)2(phen)]Cl⋅2H2O (1⋅2H2O) and [CoIII(pao)2(bpy)]Cl⋅1.5MeOH (2⋅1.5MeOH). The structures of the complexes were determined by single-crystal X-ray crystallography. The CoIII ions are six-coordinate, surrounded by three bidentate chelating ligands, that is, two pao- and one phen or bpy. The deprotonated oxygen atom of the pao- ligand remains uncoordinated and participates in hydrogen bonding with the solvate molecules. IR data of the complexes are discussed in terms of the nature of bonding and the known structures.